Environmental perception: An assessment of an experimental basic design atelier for students of architecture - Gokan, Koray (Acta Structilia, 2003)
First year architecture students participating in a basic design atelier are assessed in ’visual design activities’. In several assignments students were expected to acquire and to visualize their ’environment’. Visual design activities are derived from perceived environmental phenomena. Such activities are also based on students’ own yet limited experience in visual expressions. Basic Design is dependent upon the masterly use of students’ own vision. The information gained from physical aspects of phenomena is substantial to understand their formal and spatial functioning. Students’ personalities and preferences are inevitably involved in building aesthetic decisions. Students are expected to gain experience in changes in ’art and design’, as well as ’environment and space’. The progress is witnessed in: a) The development of personal inquiry following several trials; b) intuitive and analytical work; c) responses to environmental changes; d) subjective preferences and aesthetic judgments.